La gouvernance conflictuelle relative à la cogestion des saumons dans le bassin du fleuve Columbia (États-Unis) - Nicolas Barbier (VertigO)
In the U.S. portion of the Columbia Basin, salmon populations are five times lower than 150 years ago. They are co-managed by federal, state and tribal protagonists in order to restore them. On this territory larger than France, the federal government dominates the governance relating to the co-management of endangered and threatened species of salmon. The NOAA Fisheries Service writes up recovery plans and biological opinions that guide the actions on the ground. State and tribal agencies carry out multiple tasks on the ground, including the reintroduction of local salmon populations, the restoration of riparian areas, the management of salmon hatcheries or the enforcement of fishing rules. At the same time, a federal court in Oregon has authority to change the federal plans and biological opinions if the latter do not comply with the 1973 Endangered Species Act. During the 2000s, this court notably contributed to reduce the lethal impact of dams on salmon. If some local salmon populations have been partially restored, major problems remain unresolved : large dams keep hindering the overall recovery, just like continuing pollution and environmental degradation in parts of watersheds. Conflicts of interest between different groups go on. Environmental and fishing groups as well as Indian tribes call for more ambitious recovery targets. They come up against major agricultural and industrial interests generally protected by federal and state governments. These two governmental protagonists are opposed to the development of elements of tribal projects related to salmon hatcheries. The adoption of the United Nations Declaration on the Rights of Indigenous Peoples by the Obama administration in 2010 could defuse conflicts and bring about changes in the governance.